Qualitative Study of Biological, Psychological, Social and Spiritual Needs in Chronic Mental Patients - Sara Mokhtari; Milad SabzehAra Langaroudi; Masoume Maleki Pirbazari (Journal of Modern Psychology, 2022)
The purpose of this research is to qualitatively investigate the biological, psychological, social and spiritual needs of chronic mental patients. This research was conducted using qualitative content analysis. A number of 23 chronic mental patients referred to Tahereh Neuropsychiatric Rehabilitation Center in Ramsar city in 2021 were selected by purposive sampling method until theoretical data saturation and were subjected to semi-structured interviews. Analysis and coding of the interviews showed four components with 26 sub-components. The biological needs component includes 6 sub-components: medical costs, lack of medicine, diet, exercise and physical activity, and physical and functional problems. The mental needs component of patients includes 7 sub-components: the presence of co-comorbidity, experiencing unpleasant emotions, lack of personal and social skills, lack of positive psychological characteristics, low quality of life and psychological exhaustion, and having fun and free time. The social needs component of patients includes 7 sub-components: need for family support, need for support from relevant organizations, lack of social facilities, social stigma, possibility of education, possibility of employment and need for support from specialists. The component of patients' spiritual needs also includes 6 sub-components: the need to have hope, perform religious rituals, lack of meaning and purpose in life, fear of death, loneliness and attitude towards God. The obtained findings show that there are different needs in the 4 biological, psychological, social and spiritual dimensions that must be paid attention to in order to improve the mental health and quality of life of chronic mental patients.